2023
DOI: 10.3390/agronomy13082093
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Application of Biological Agent and Fertilizer on Fungal Community Structure in Rhizosphere Soil of Panax notoginseng

Abstract: The fungal community structure and soil fertility in rhizosphere soil have an important effect on the health of Panax notoginseng (P. notoginseng). The attack of pathogenic fungi and the imbalance of soil fertility can easily lead to diseases. The effect of Bacillus subtilis on improving the community structure of soil fungi has been confirmed, and the corresponding biological agent products have been commercialized. A pot experiment carried out in a greenhouse explored the effect of a biological agent and fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
1
0
0
Order By: Relevance
“…At the gate level, different treatments did not change the dominant gate in the rhizosphere soil of Panax notoginseng. Ascomycota, Basidiomycota and Mortierellomycota were still the dominant gates in the soil, a finding similar to the results of previous studies [29,30]. In previous reports, Fusarium, Cylindrocarpon, Ilyonectria and other pathogenic bacteria were the dominant bacteria in the rhizosphere soil of perennial Panax notoginseng [31,32].…”
Section: Discussionsupporting
confidence: 89%
“…At the gate level, different treatments did not change the dominant gate in the rhizosphere soil of Panax notoginseng. Ascomycota, Basidiomycota and Mortierellomycota were still the dominant gates in the soil, a finding similar to the results of previous studies [29,30]. In previous reports, Fusarium, Cylindrocarpon, Ilyonectria and other pathogenic bacteria were the dominant bacteria in the rhizosphere soil of perennial Panax notoginseng [31,32].…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the TOPSIS model was used to evaluate the maize yield and fertilizer use efficiency of five P treatments in saline-alkali soil. Previous studies have shown that TOPSIS can provide an effective solution for optimizing various traits and a comprehensive evaluation of multiple populations [30,33,57,58]. The TOPSIS model in this study showed that T3 ranked 1st and T4 ranked 2nd in the 2018 season.…”
Section: Discussionmentioning
confidence: 54%